(untitled) (Journal of the College of Basic Education, 2022)
Abstract The aim of this work is synthesis of Poly (Vinyl-4-AminoBenzoate) (PVAB) from reaction of PVA with 4-aminobenzoyl chloride in alkaline media. We also prepare the metal complexes of poly (vinyl-4-aminobenzoate) and antimicrobial properties were evaluated by dilute method against five pathogenic bacteria (Escherichia coli, Shigella dysentery, Klebsiella pneumonae, Staphylococcus aureus, Staphylococcus Albus) and two fungal (Aspergillus Niger, Yeast). All polymer metal complexes showed different activities against the various microbial isolates. The polymer metal complexes showed higher activity than the free polymer.